Aries - Moorey, Teresa (Reach your potential., 1998)
This guide aims to help Arien readers reach their full potential by examining their star sign, making the most of their assets, benefitting from their weak points, excelling at work and succeeding in relationships. It also describes how compatible Ariens are with every other birth sign.